Kinetics of badminton lunges in four directions - Hong, Y.; Jun Wang, S.; Kai Lam, W.; Tak-Man Cheung, J. (Journal of Applied Biomechanics, 2014)
The lunge is the most fundamental skill in badminton competitions. Fifteen university-level male badminton players performed lunge maneuvers in four directions, namely, right-forward, left-forward, right-backward, and left-backward, while wearing two different brands of badminton shoes. The test compared the kinetics of badminton shoes in performing typical lunge maneuvers. A force plate and an insole measurement system measured the ground reaction forces and plantar pressures. These measurements were compared across all lunge maneuvers. The left-forward lunge generated significantly higher first vertical impact force (2.34 ± 0.52 BW) than that of the right-backward (2.06 ± 0.60 BW) and left-backward lunges (1.78 ± 0.44 BW); higher second vertical impact force (2.44 ± 0.51 BW) than that of the left-backward lunge (2.07 ± 0.38 BW); and higher maximum anterior-posterior shear force (1.48 ± 0.36 BW) than that of the left-backward lunge (1.18 ± 0.38 BW). Compared with other lunge directions, the left-forward lunge showed higher mean maximum vertical impact anterior-posterior shear forces and their respective maximum loading rates, and the plantar pressure at the total foot and heel regions. Therefore, the left-forward lunge is a critical maneuver for badminton biomechanics and related footwear research because of the high loading magnitude generated during heel impact.